2022
DOI: 10.12934/jkpmhn.2022.31.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Nursing Students' Therapeutic Use of Self in Web-Based Psychiatric Nursing Practicum Focusing on Role-Playing

Abstract: Purpose: This study aimed to explore the experiences of nursing students' therapeutic use of self in web-based psychiatric nursing practicum focusing on role-playing.Methods: The participants were 13 senior nursing students who had underwent three weeks of web-based psychiatric nursing practicum. Data were collected through in-depth video interviews, and analyzed using the grounded theory method, developed by Strauss and Corbin (1998).Results: In total, 14 categories and 29 sub-categories were generated. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…As an alternative, role-plays or standardized patients can be used to enhance communication skills and interview techniques that are required in mental health nursing practicums, specifically during times when clinical practicum experiences are limited. These approaches could reduce students’ tensions and anxieties while boosting their confidence in clinical practice [ 10 , 32 , 33 , 34 ]. Therefore, role-play clinical simulations should be considered to develop effective coping strategies, communication skills, and teamwork skills among learners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative, role-plays or standardized patients can be used to enhance communication skills and interview techniques that are required in mental health nursing practicums, specifically during times when clinical practicum experiences are limited. These approaches could reduce students’ tensions and anxieties while boosting their confidence in clinical practice [ 10 , 32 , 33 , 34 ]. Therefore, role-play clinical simulations should be considered to develop effective coping strategies, communication skills, and teamwork skills among learners.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health nursing practicums are designed to provide nursing students the competence to develop positive therapeutic relationships with people experiencing mental disorders through communications training [ 9 ]. However, during the COVID-19 pandemic, psychiatric care facilities restricted nursing students’ access to the psychiatric wards due to the infection-prone contamination on these floors [ 10 ]. As a result, virtual simulation programs were adopted to replace the mental health nursing practicum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants recognized the importance of communication and the need to be prepared to form a therapeutic patient-nurse relationship in the clinical practice setting. Yang [22] found that communication skills were the most influential factor on nursing students' clinical practice stress. Hyun & Seo [21] reported that nursing students have fear of forming relationships with patients before psychiatric nursing practicum, but their attitudes toward mental illness changed after completing both lectures and practicum [23].…”
Section: Discussionmentioning
confidence: 99%
“…간호학에서 역할극을 활용한 교육은 학습 자를 몰입시키는 참여형 시뮬레이션 교육의 한 형태로 [30], 실질적으로 인간관계 및 의사소통 상황을 경험하고 적용해 볼 수 있다 [22]. 역할극을 활용한 교육은 다른 사 람의 역할을 경험하여 자신이나 타인의 행동에 대한 새로 운 통찰력을 제공하고 환자의 입장을 이해하도록 해 공감 능력을 향상시킬 수 있어, 대인관계능력, 의사소통 능력 함양에 효과적인 것으로 나타났다 [21,31] [20,23,24]. 국내 의사소통 교육은 신규 간호사 를 대상으로 비폭력 대화 교육 프로그램을 수행하였다.…”
Section: ) 역할극을 활용한 온라인 기반 의사소통 교육unclassified